Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

simplify. e^(in x)=, e^(in 5)=, e^(in 3x)=

Sagot :

Answer:

Step-by-step explanation:

e^ lnx  = x

e^ ln5 = 5

e^ ln 3x = 3x

I think you get the idea... e is an inverse operation to ln  :o

Answer:

x

5

3x

Step-by-step explanation: